New insights into the biology of Calanus spp. (Copepoda) males in the Arctic - Daase, Malin; Kosobokova, Ksenia; Last, Kim S; Cohen, Jonathan H.; Choquet, Marvin; Hatlebakk, Maja Karoline Viddal; Søreide, Janne (Marine Ecology Progress Series, 2018)
Source at https://doi.org/10.3354/meps12788 . Adult males of Calanus copepods in the Arctic are mainly observed between late autumn and late spring, and are seldom recorded during summer. Due to logistical constraints, there are still relatively few studies on zooplankton in high-latitude regions during the winter, and subsequently, little is known about Calanus males. Here, we present data on abundance, spatial distribution, prosome length, lipid content, respiration and swimming activity of i>Calanus adults, along with adult sex ratios in i>Calanus populations from 5 Arctic fjords in Svalbard, Norway (78-80° N) during the polar night in January 2015, 2016 and 2017. Adult males and females of i>Calanus were observed at all locations and occurred throughout the entire water column. Morphological examination and molecular identification of i>Calanus males proved that all males encountered belong to Calanus glacialis , even in the fjords where overwintering copepodite stage CV of C. finmarchicus dominated at the time. Adult sex ratios in C. glacialis populations varied from 1 male per 4 females to 2 males per female. From 3 to 18% of females carried spermatophores attached to the genital segment. Lipid content in males was slightly higher than in females. Shipboard experiments showed that males had higher swimming activity and respiration rates than females. Our observations indicate that adult males of C. glacialis stay active and demonstrate active mating behavior in mid-winter, and that the mating phenology of C. glacialis is decoupled from that of C. finmarchicus in the study area in January.